The correlation between vitamin D and levels of IFN-γ, NF-κB, thyroid antibodies in down syndrome: study in Indonesian children - Hisbiyah, Yuni; Endaryanto, Anang; Setyoboedi, Bagus; Rochmah, Nur; Faizi, Muhammad (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Vitamin D (VD) reduces interferon-gamma (IFN-γ) production and prevents nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) activation, impacting the inhibition of the autoimmunity process such as autoimmune thyroiditis (AITD). Children with Down syndrome (DS) are reported to have a higher risk of autoimmunity and lower VD levels than non-DS. Therefore, this study aimed to evaluate VD levels in Indonesian DS children and their relationship with marker of AITD. Methods: This study was conducted on DS children at Dr Soetomo Hospital between February 2021-June 2022. Socio-demographic status, amount of milk, fish and meat consumption, and duration of sun exposure were obtained using a self-report questionnaire. Thyroid hormone (TSH and FT4), thyroid antibody (TPO-Ab and Tg-Ab), 25 (OH)D, IFN-γ, and NF-κB levels were measured using ELISA. Results: Of the 80 participants, 53.75% had sufficient (50.829±17.713 ng/ml) and 46.25% had non-sufficient (20.606±5.974 ng/ml) VD levels. Daily milk consumption, meat and fish consumption were risk factors contributing to VD levels in multivariate analysis [p=0.003, OR=1.007(1.003–1.012); p=0.004, OR=1.816(1.209– 2.728), respectively]. Participants with sufficient VD had significantly higher TPO-Ab (p=0.007) and Tg-Ab (p=0.016). Mean of VD levels were significantly negatively correlated with IFN-γ levels (r =-0.262, p=0.037) and positively correlated with TPO-Ab (r= 0.432, p=1x10-5,) and Tg-Ab (r= 0.375, p=0.001). Conclusions: Majority of subjects had sufficient VD levels. VD suppresses IFN-g, but is unable to affect NF-κB levels, presumably causing high levels of TPO-Ab and Tg-Ab in sufficient VD patient.